A new risk variant for multiple sclerosis at the immunoglobulin heavy chain locus associates with intrathecal IgG, IgM index and oligoclonal bands. (August 2015) - Delgado-García, Mercedes; Matesanz, Fuencisla; Alcina, Antonio; Fedetz, María; García-Sánchez, María Isabel; Ruiz-Peña, Juan Luis; Fernández, Óscar; Pinto Medel, María Jesús; Leyva, Laura; Arnal, Carmen; Delgado, Concepción; López Guerrero, José Antonio; et al.
Background: Recent findings have shown a correlation between the intrathecal IgG index and variants at the immunoglobulin heavy chain (IGHC) locus in patients with multiple sclerosis (MS). Objectives: The objective of this paper is to analyse the association of the locus with MS susceptibility and its relationship with intrathecal immunoglobulin (Ig) parameters. Methods: We genotyped the rs11621145 variant, located at the IGHC locus, in 2726 patients with MS and 2133 healthy controls. Associations of intrathecal IgG and IgM indexes with rs11621145 were analysed by linear regression analysis in 538 MS patients. Results: We found that rs11621145 showed statistically significant evidence for association with susceptibility to MS (odds ratio = 0.69, p = 1.053E-09), though validation of this result in additional cohorts would be desirable. We confirmed the association between the IgG index and the rs11621145 ( p = 6.85E-07, Beta = 0.207). Furthermore, rs11621145 was inversely correlated with IgM index ( p = 7.24E-04, Beta = -0.277), and therefore marks a decreased likelihood of presenting IgM oligoclonal bands (odds ratio = 0.38, p = 2.35E-06). Conclusions: Our results suggest that the polymorphism of the IGHC locus could be altering the switching of the Ig isotype in B cells and it may be interfering with T-dependent and T-independent antibody responses.